Evolution of sample-based music authorship network - Dongju Park; Juyong Park (EPJ Data Science)
Abstract Sample-based music—characterized by the adoption of extant audio fragments (sampling) in its creation process—plays an essential role in contemporary popular music, fostering inter-generational connections between the creators that have resulted in a rich and diverse sonic landscape. The selection, manipulation, and adoption of samples heavily impact the genre, mood, texture, and finally the distinctive identity of a new musical composition. One could call the samples “cultural genes” of sorts, continually incorporated into new music to contribute to its characteristics. One can then ask how this process has taken place in history and shaped the history of contemporary popular music, which we study in this work. We specifically study the evolution of sample-based music between the years 1980 and 2019, taking cue from the citation network analysis of academic literature that intuitively follows a similar dynamic of the flow of ideas and material from the old works into new ones. First, the community structure in the artist–sample network is identified, and its relationship to distinctive musical styles and flavors is verified. A longitudinal analysis of the passing down of musical styles is then performed based on similarity between communities of distinct eras, identifying continuous temporal developments in music as well as instances of the revival of styles dormant across multiple generations, akin to “genetic atavism.” This study demonstrates the complex nature of cultural evolution using a network framework that is also generally applicable to other creative enterprises.